2006
DOI: 10.1152/ajpheart.01014.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic activation of peroxisome proliferator-activated receptor-α or high-fat feeding in a rat infarct model of heart failure

Abstract: Intracardiac accumulation of lipid and related intermediates (e.g., ceramide) is associated with cardiac dysfunction and may contribute to the progression of heart failure (HF). Overexpression of nuclear receptor peroxisome proliferator-activated receptor-alpha (PPARalpha) increases intramyocellular ceramide and left ventricular (LV) dysfunction. We tested the hypothesis that activation of fatty acid metabolism with fat feeding or a PPARalpha agonist increases myocardial triglyceride and/or ceramide and exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 39 publications
3
62
0
1
Order By: Relevance
“…The current authors speculate that WY protected the lungs from PAF-induced permeability due inhibition of the PGE 2 (COX-1) or ceramide (ASM) pathway [36]. Evidence is accumulating that activation of PPAR-a induces an increase in ceramides, although these data were generated in hearts and not in lungs [37,38]. Taking this together with the reduction in PGE 2 as determined in the BAL after LPS challenge in vivo, the COX-1 and COX-2 pathways can be considered primary targets of PPAR-a in effects on permeability in the present model.…”
Section: Discussionmentioning
confidence: 89%
“…The current authors speculate that WY protected the lungs from PAF-induced permeability due inhibition of the PGE 2 (COX-1) or ceramide (ASM) pathway [36]. Evidence is accumulating that activation of PPAR-a induces an increase in ceramides, although these data were generated in hearts and not in lungs [37,38]. Taking this together with the reduction in PGE 2 as determined in the BAL after LPS challenge in vivo, the COX-1 and COX-2 pathways can be considered primary targets of PPAR-a in effects on permeability in the present model.…”
Section: Discussionmentioning
confidence: 89%
“…However, reactivation of PPAR␣ by a selective agonist in the heart in different models of heart failure has yielded diverse effects. Rats treated with a PPAR␣ agonist and subjected to pressure overload-induced hypertrophy developed contractile dysfunction (40), whereas a rat model of postinfarction heart failure showed enhanced LV hypertrophy but with no apparent deterioration of cardiac function (41). These results indicate that the different etiologies of heart failure respond differently on PPAR␣ activation, probably due to diverse regulation of cardiac substrate metabolism.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies have reported that neither a high saturated or polyunsaturated fat diet altered cardiac mass or adversely affected cardiac function. A diet high in lard (a mix of saturated and unsaturated fat) did not further compromise cardiac function after infarction-induced HF (27), whereas a high saturated fat diet prevented HF and death associated with chronic hypertension (28,40,44). Interestingly, it may be the carbohydrate composition of a diet, and not fats, that have the greater impact based on evidence linking increased glycemic load to greater cardiovascular risk (8), a concept that demands further investigation.…”
Section: Discussionmentioning
confidence: 99%